PENGARUH DISKON DAN HADIAH TERHADAP PENGGUNAAN KARTU KREDIT (STUDI PADA PEMANDIRING KARTU KREDIT BANK MANDIRI CABANG MATARAM) - DEWI, BAIQ RENI SARI (Universitas Mahasaraswati Mataram, 2019)
This study aims to find out the significant influence both partially and simultaneously and which variables have the most dominant influence from discounts and prizes on the use of credit cards of Bank Mandiri branch Mataram. This type of research is associative research, with a population of credit card holders of the Bank Mandiri branch in Mataram. The sampling technique used in this study is accidental sampling with a sample of 60 respondents. With data collection techniques and tools in the form of a questionnaire, a score is obtained which refers to the use of a Likert scale. To find out the results of calculations according to the regression equation, statistical tests are carried out, namely f test and t test as a hypothesis test tool. The results of the analysis show that both are 1). Partially giving discounts and prizes has a significant effect on the use of Bank Mandiri credit cards in the city of Mataram. This is evidenced by the probability value of each variable smaller than 0.05. 2) Simultaneously giving discounts and gifts has a significant effect on the use of Bank Mandiri credit cards in the city of Mataram. This is evidenced by the probability of a value of f that is smaller than 0.05